DUBs, New Members in the Hypoxia Signaling clUb - Schober, Amelie S.; Berra, Edurne (Frontiers in Oncology, 2016)
Cellular protein homeostasis is tightly regulated by ubiquitination. Responsible for target protein ubiquitination is a class of enzymes, the so-called ubiquitin (Ub) E3-ligases. They are opposed to a second class of enzymes, called DeUBiquitinating enzymes (DUBs), which can remove polyubiquitin chains from their specific target proteins. The coaction of the two sets of enzymes allow the cell to adapt its overall protein content and the abundance of particular proteins to a variety of cellular and environmental stresses, including hypoxia. In recent years, DUBs have been highlighted to play major roles in many diseases, including cancer, both as tumor suppressors and oncogenes. Therefore, DUBs are emerging as promising targets for cancer-cell specific treatment. Here, we will review the current understanding of DUBs implicated in the control of hypoxia-inducible factor (HIF), the regulation of DUBs by hypoxia and the use of DUB-specific drugs to target tumor hypoxia signaling.